Iterative analysis of cerebrovascular reactivity dynamic response by temporal decomposition. Issue 9 (26th July 2017) - van Niftrik, Christiaan Hendrik Bas; Piccirelli, Marco; Bozinov, Oliver; Pangalu, Athina; Fisher, Joseph A.; Valavanis, Antonios; Luft, Andreas R.; Weller, Michael; Regli, Luca; Fierstra, Jorn
Abstract: Objective: To improve quantitative cerebrovascular reactivity (CVR) measurements and CO2 arrival times, we present an iterative analysis capable of decomposing different temporal components of the dynamic carbon dioxide‐ Blood Oxygen‐Level Dependent (CO2 ‐BOLD) relationship. Experimental Design: Decomposition of the dynamic parameters included a redefinition of the voxel‐wise CO2 arrival time, and a separation from the vascular response to a stepwise increase in CO2 (Delay to signal Plateau – DTP) and a decrease in CO2 (Delay to signal Baseline –DTB). Twenty‐five (normal) datasets, obtained from BOLD MRI combined with a standardized pseudo‐square wave CO2 change, were co‐registered to generate reference atlases for the aforementioned dynamic processes to score the voxel‐by‐voxel deviation probability from normal range. This analysis is further illustrated in two subjects with unilateral carotid artery occlusion using these reference atlases. Principal Observations: We have found that our redefined CO2 arrival time resulted in the best data fit. Additionally, excluding both dynamic BOLD phases (DTP and DTB) resulted in a static CVR, that is maximal response, defined as CVR calculated only over a normocapnic and hypercapnic calibrated plateau. Conclusion: Decomposition and novel iterative modeling of different temporal components of the dynamic CO2 ‐BOLD relationship improves quantitative CVR measurements. Abstract : CO2 time evolution versus BOLD signal in two illustrative voxels using different methodological time shifts. It shows the results of the novel iterative analysis to decompose three dynamic temporal components of the CO2‐BOLD relationship, resulting in the most optimal fit.